Fundamentals of research in criminology and criminal justice - Bachman, Ronet (SAGE, 2012)
"Fundamentals of Research in Criminology and Criminal Justice is a concise resource for understanding the multifaceted subject of research methods in the field of criminology and criminal justice. This book uniquely helps to teach research design and techniques within the context of substantive criminology and criminal justice issues of interest to students and the field. This is a briefer version of Ronet and Russ's successful The Practice of Research in Criminology and Criminal Justice, written in a less formal style, with more concise examples drawn from everyday experience, and less coverage of complex or more rigorous methods. This is an excellent introductory methods text for undergraduate research courses in the fields of Criminal Justice and Criminology. It is ideal for students who need to understand how criminal justice research is done and appreciate the results, but may never do research themselves in the professional lives"--